Intraoperative sensitization in trigeminal region caused by postherpetic neuralgia: a case report - Gangwen Guo; Dan Li; Hongyan Li; Rong Hu; Haocheng Zhou (Journal of Medical Case Reports)
Abstract Background Interventional therapy of trigeminal neuropathic pain has been well documented; however, intraoperative monitoring and management of pain hypersensitivity remains barely reported, which may pose a great challenge for pain physicians as well as anesthesiologists. Case presentation A 77-year-old Han Chinese male, who suffered from severe craniofacial postherpetic neuralgia, underwent pulsed radiofrequency of trigeminal ganglion in the authors’ department twice. The authors successfully placed a radiofrequency needle through the foramen ovale during the first procedure with local anesthesia and intravenous sedation (dexmedetomidine). The patient reported about 50% pain reduction postoperatively, and the second procedure was performed 1 week later. However, the intraoperative administration of sedative agents was suspended owing to hemodynamic instability during the second session. As a result, the patient displayed hypersensitivity to the percutaneous operation under local anesthesia and the authors failed to place the needle inside the Meckel’s cave for uncontrollable breakthrough pain. The patient still needed to take oral medication for pain control, oxycodone (10–20 mg, every 12 hours) and pregabalin (75 mg, two times a day) in the last follow-up at 1.5 years after discharge. Conclusion The authors report a failure case of percutaneous puncturing operation with trigeminal neuropathic pain, potentially caused by intraoperative sensitization. It is essential to monitor and prevent hypersensitivity to both innoxious and noxious stimuli in patients with neuropathic pain syndrome, especially at surgical sites close to the area of nerve injury.